4+2(3x-6)=5-3(2x+1)

Simple and best practice solution for 4+2(3x-6)=5-3(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+2(3x-6)=5-3(2x+1) equation:


4+2(3x-6)=5-3(2x+1)

We simplify the equation to the form, which is simple to understand
4+2(3x-6)=5-3(2x+1)

Reorder the terms in parentheses
4+(+6x-12)=5-3*(2x+1)

Remove unnecessary parentheses
+4+6x-12=+5-3+*(+2x+1+)

Reorder the terms in parentheses
4+6x-12=5+(-6x-3)

Remove unnecessary parentheses
+4+6x-12=+5-6x-3

We move all terms containing x to the left and all other terms to the right.
+6x+6x=+5-3-4+12

We simplify left and right side of the equation.
+12x=+10

We divide both sides of the equation by 12 to get x.
x=0.833333333333

See similar equations:

| 2+4(5x-6)=9-5(2x+1) | | 8x-7(-88/41)=13 | | N=60t-6t^2 | | 7x-y=15 | | -5(13+7y)-6y=23 | | 11x-99=11 | | 8x+6=6(x+7) | | 0.3x-5=0.1(x+10) | | 3x^2-39x=0 | | Y-9-y+5=8y | | 1200=7v*v+300 | | y=7v*v+300 | | .4x+.6y=24 | | 13m^2+39m=0 | | sx+ty=u | | z^4-1=0 | | x-9/2-3=x-8/3 | | 11x/14-9=x/7+36 | | x/4+x/5=9/20 | | 0=-16t^2+vt+c | | 2n/3-7/13=31/39 | | 4c+1=32 | | x/4-3=-8 | | 9(z+3)-2(z-4)=3(z-4)+3(z-1) | | 9(z+3)-2(z-4)=3(z-1) | | 2x^3+x-18=0 | | -9x+4y=14 | | X^2=y+12 | | 8x=36x | | 500-335= | | 48t^2-28t+2=0 | | 2x^2+10x=-6 |

Equations solver categories